Archiwum TVP a programy publicystyczno-kulturalne o tematyce filmowej. Lata 1989–2020 - Drewniak, Mateusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article analyses the content and availability of audio-visual archives of Polish Public Television regarding TV shows devoted to film and cinema productions broadcast between 1989 and 2020. This study allows general conclusions to be formulated that concern the research opportunities that this particular archive generates mostly for film and media scholars. Apart from presenting the results of in-depth analysis of archives, the text inscribes these reflections into the latest studies on archives, as well as into discussions on contemporary TV film criticism.